Leveraging Digital Twins as a Common Operating Picture for Disaster Management: Case of Seismic Hazards - Mustafa Korkmaz; A. Can Zulfikar; Sevilay Demirkesen (ISPRS International Journal of Geo-Information)
Disasters, both natural and man-made, pose significant challenges that necessitate swift and informed decision-making to minimize impacts and enhance recovery efforts. This study explores the integration of digital twins (DTs) with a common operating picture (COP) to improve disaster management practices, particularly during the response phase. Utilizing a comprehensive approach, the research develops a 3D core model of Kocaeli, Turkey, which incorporates real-time data from various sources, including building information models and seismic hazard assessments. The findings reveal that the DT–COP framework significantly enhances situational awareness and resource allocation, allowing for more effective response strategies. However, challenges related to data accuracy, integration, and interoperability persist. The study concludes that leveraging DTs as a COP can transform disaster management practices, ultimately improving response capabilities and community resilience while highlighting the need for ongoing research to address existing challenges.